Caretakers' perceptions and willingness‐to‐pay for complementary food in urban and rural Cambodia - Nurhasan, M.; Prima, R.A.; Olsen, S.B.; Wieringa, F.T.; Dijkhuizen, M.A.; Chamnan, C.; Roos, N. (Wiley, 2021)
Inadequate child nutrition during the first ‘1000 days’ is widespread in Cambodia, resulting in a high prevalence of child malnutrition. Access to processed complementary food in packages (PCFP) may support caretakers in improving diet of young children. This study aimed to evaluate the caretakers' preferences and willingness‐to‐pay (WTP) for PCFP in Cambodia. The study was conducted in urban and rural settings, involving 520 caretakers with children aged 7–24 months in Phnom Penh (urban) and Prey Veng (rural). Four PCFPs were included: a commercial brand, a social‐commercial brand, a worldwide distributed fortified complementary food aid product (CSB++) and an experimental fortified rice‐and‐fish‐based PCFP developed in Cambodia (WF‐L). Sensory analysis was conducted for all products, stated WTP was assessed for three products (excluding CSB++) and actual WTP experiment was conducted on WF‐L only. Our results show that overall, WF‐L was preferred by the rural participants over food aid CSB++. Further improvements in the organoleptic qualities of WF‐L should focus on consistency and taste. The participants were, on average, willing to pay 1,667 Cambodian riel (KHR, $0.4) and 1,192 KHR ($0.3) in urban and rural settings, respectively, for 35 g of WF‐L. We also found that despite being nutritionally inadequate, most participants considered homemade porridge to be healthier, more practical and preferred by the children. Therefore improving the quality of homemade foods merits urgent consideration. When applying PCFP in nutrition programmes as a supplementary option to homemade complementary foods, locally produced products could be a more viable supplementary option than global food aid.